The Modification of LMS Quipperschool to Improve Senior High School Students’ Concept Mastery of Biology Subject, Topic: Human Reproduction Health - Muhammad Luthfi Hidayat (Journal of Educational Science and Technology (EST), 2018)
This research aims to: (1) develop a biology Learning Management System (LMS) in Human Reproduction System Health with Quipper School platform, (2) develop an instrument of biology to improve student’s concept mastery at SMA Muhammadiyah I Klaten. This developmental research referred to the design and development research (DDR) model suggested by Richey & Klein (2007) grouped into six developmental procedures, and simplified into five procedures including (a) identifying the problem, (b) describing the objectives, (c) designing and developing product, (d) testing and evaluating product, (e) communicating the testing results. The data were analyzed using the parametric statistical model of ANCOVA test with the significance level of 0.05.  The research finding reveals that the implementation of the LMS is in the “very good” category. There is a significant difference in the concept mastery (p=0.013) between the experimental and control class after the use of Human Health Reproduction LMS  with p < 0.05. The conclusion of this research is that the use of LMS of Human Health Reproduction is able to improve the concept mastery of students